2013
DOI: 10.1152/ajpheart.00805.2012
|View full text |Cite
|
Sign up to set email alerts
|

Blunted temporal activity of microvascular perfusion heterogeneity in metabolic syndrome: a new attractor for peripheral vascular disease?

Abstract: Butcher JT, Goodwill AG, Stanley SC, Frisbee JC. Blunted temporal activity of microvascular perfusion heterogeneity in metabolic syndrome: a new attractor for peripheral vascular disease? Am J Physiol Heart Circ Physiol 304: H547-H558, 2013. First published December 21, 2012 doi:10.1152/ajpheart.00805.2012.-A key clinical outcome for peripheral vascular disease (PVD) in patients is a progressive decay in skeletal muscle performance and its ability to resist fatigue with elevated metabolic demand. We have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Going forward, recent studies have shed new light on microvascular dysfunction itself that may represent a more accurate predictor of poor outcomes in OZR than has been available previously. Specifically, previous studies have identified an attractor that integrates vascular hemodynamics and reactivity at successive arteriolar bifurcations to create a condition in which terminal arteriolar perfusion becomes both increasingly heterogeneous and less responsive to changes in the local environment (5,21).…”
Section: Linking Peripheral Vascular Disease (Pvd) Risk To Integratedmentioning
confidence: 99%
“…Going forward, recent studies have shed new light on microvascular dysfunction itself that may represent a more accurate predictor of poor outcomes in OZR than has been available previously. Specifically, previous studies have identified an attractor that integrates vascular hemodynamics and reactivity at successive arteriolar bifurcations to create a condition in which terminal arteriolar perfusion becomes both increasingly heterogeneous and less responsive to changes in the local environment (5,21).…”
Section: Linking Peripheral Vascular Disease (Pvd) Risk To Integratedmentioning
confidence: 99%
“…Therefore, not only does sympathetic inhibition improve total flow, it also improves blood flow distribution. However, this is only true in the proximal circulation [at the level of 1A-2A arterioles, (4, 14)] (Figure 4A and B). …”
Section: Introductionmentioning
confidence: 99%
“…Similar to obese subjects, OZ rats exhibit central obesity, insulin resistance, hyperlipidemia, and cardiovascular dysfunction (9,46). We have previously shown that, compared with LZ rats, OZ exhibit exacerbated systemic inflammation and acute lung injury (ALI) after severe trauma (48).…”
mentioning
confidence: 99%